Matrix Calculator: An Innovative Approach to Balancing Chemical Equations - Zussette Candelario-Aplaon; Dionisio E. Briñosa (Research Synergy Foundation, 2026)
In the New Normal, higher education institutions are using Remote Emergency Teaching instead of face-to-face instruction. However, due to academic disruptions and abrupt shifts in learning modalities, teachers and students are encountering difficulties. Challenges are even greater in teaching and learning complex topics like balancing equations. Because of this, Chemistry teachers are devising plans and finding innovative ways to deliver effective instruction amidst pandemics. Using collaborative action research with mixed methods, this study aimed to improve the teaching and learning of balancing chemical equations in the New Normal. As an intervention strategy, the concept of the matrix in Linear Algebra is integrated. This study is the Phase II of the previously conducted expository research about balancing equations using Gauss-Jordan Elimination aided by Matrix Calculator. The mixed method design employed was the embedded approach. Fifty-two students enrolled in Organic Chemistry took part in the study. They were taught through team teaching, using traditional computation and the Matrix Calculator. They were given a test before and after the intervention, and their scores were treated using the mean and paired t-test. Ten students were selected and interviewed online. The responses during the interview were transcribed and analyzed through thematic coding. The results showed a significant difference between the pretest and post-test scores, indicating that Matrix Calculator is an effective tool for teaching and learning to balance chemical equations. Among the themes that emerged are accessibility, usability, and accuracy. Furthermore, the results indicated the need for a self-instructional module to support independent and flexible learning.